Patient experiences using a novel tool to improve care transitions in patients with heart failure: a qualitative analysis - Toni Schofield; Cindy Yin; Shoshana Hahn-Goldberg (BMJ Open, 2019)
ObjectiveTo evaluate the utility of a novel discharge tool adapted for heart failure (HF) on patient experience.DesignSemistructured interviews assessed the utility of a novel discharge tool adapted for HF; patient-oriented discharge summary (PODS-HF) at 72 hours and 30 days after leaving hospital. Interviews were recorded and transcribed verbatim. Three investigators used directed content analysis to determine themes and subthemes from the narrative data.SettingThe cardiology ward of an urban academic institution in Canada.Participants13 patients and caregivers completed 24 interviews. Eligible patients were >18 years and admitted with a diagnosis of HF.ResultsAnalysis revealed six interconnected themes: (1) Utility of discharge instructions: how patients perceive and use written and verbal instructions. Patients receiving PODS-HF identified value in the patient-centred summarised content. (2) Adherence: strategies used by patients to enhance adherence to medications, diet and lifestyle changes. PODS-HF provides a strong visual reminder, particularly early postdischarge. (3) Adaptation: how patients incorporate changes into ‘new norms’. This was more evident by 30 days, and those using PODS-HF had less unscheduled visits and readmissions. (4) Relationships with healthcare providers: patients’ perceptions of the roles of family physicians and specialists in follow-up care. (5) Role of family and caregivers: the pivotal role of caregivers in supporting adherence and adaptation. (6) Follow-up phone calls: the utility of follow-up calls, particularly early after discharge as a means of providing clarification, reassurance and education.ConclusionPODS-HF is a useful tool that increases patients’ confidence to self-manage and facilitates adherence by providing relevant written information to reference after discharge.